IDENTIFIKASI KELAYAKAN USAHA ARKAN QUAIL FARM KABUPATEN BOGOR KECAMATAN CIAMPEA DESA CIHIDEUNG UDIK - Mile, Rahmat Hijriyah; Syukur, Hizkia Immanuel A; Sitopu, Evelyn Egidia; Enteding, Trianto (Fakultas Pertanian Universitas Tompotika Luwuk, 2025)
Considering the need for meat consumption continues to increase every year, the position of animal husbandry currently has bright prospects for development. On the other hand, as a source of income and growth in economic value, which is influenced by an increase in population. This study aims to determine the amount of income and business feasibility of laying quail farms in Cihideung Udik Village, Ciampea District, Bogor Regency. By using quantitative descriptive analysis method, including income analysis and financial feasibility. The results of the study obtained that the Arkan Quail Farm livestock business obtained a large enough and profitable income in one production cycle, and based on the financial feasibility analysis obtained that the livestock business was feasible to develop because the results> 1. Thus the laying quail livestock business can be used as a business for those who want to become quail business actors.